Direct determination of naturally occurring biologically active compound–serum albumin conjugate by matrix-assisted laser desorption/ionization mass spectrometry. Issue 1 (2001) - Tanaka Tanaka, H. H.; Xuan Xuan, L.J. L.J.; Morimoto Morimoto, S. S.; Shoyama Shoyama, Y. Y.; Isobe Isobe, R. R.; Nojima Nojima, K. K.
Abstract : Opium alkaloids were conjugated with bovine serum albumin (BSA) to give individual antigen conjugates which were analyzed using BSA as an internal standard by matrix-assisted laser desorption/ionization (MALDI) mass spectrometry. It became clear that 9 molecules of thebaine were conjugated in a thebaine–BSA conjugate. Codeine and morphine contents in individual conjugates were determined to be 12 and 6 molecules, respectively. Using a relative molecular mass of BSA, 11.5 molecules of forskolin conjugated with BSA. Tetrahydrocannabinolic acid (THCA)–carrier protein conjugates using β -alanine or without β -alanine as a linker were analyzed. From these results it became evident that the hapten molecules of THCA– β -alanine–BSA, THCA–BSA, THCA– β -alanine–human serum albumin (HSA) and THCA–HSA were 17.2, 12.7, 27.8 and 54.4, respectively. Crocin–HSA conjugates were synthesized by two methods using succinate and NaIO4 cleavage of sugar moiety. A broad molecular peak of crocin–HSA conjugate appeared at around m/z 98, 342 resulting in 30 molecules of crocin-hemisuccinate conjugated with HSA. The crocin–HSA synthesized via NaIO4 oxidation showed a sharp molecular peak around 69, 504 compared to that of hemisuccinate preparation. The number of crocin combined with HSA was, however, smaller 3.1 molecules. Analysis of monoclonal antibody by MALDI mass spectrometry determined the exact molecular weight and their purities.